Liver autopsy study – incidental pathological findings - Dr. Aniruddha Behera; Dr. Alaka Sahu; Dr. Salil Kumar Nayak; Dr. Kailash Chandra Agrawal (Tropical Journal of Pathology and Microbiology, 2017)
Background: Liver is the site of many diseases, many of which become symptomatic while some are diagnosed only on autopsy. Involvement of liver is secondary to cardiac, metabolic, social problem like alcoholism, drug toxicity, injudicious use of topical applications, herbal remedies and environmental exposures.Aims and Objectives: In apparently healthy individuals autopsy study sometimes reveals liver diseases. Hence this study aims at finding the frequency and the histopathological appearances in random liver autopsy, so as to evoke public awareness against alcoholism, drug toxicity and potential toxins (perfumes, shampoo, cleaning solvents, pesticides fertilizers,).Materials and Methods: The present study was carried out in the Department of Pathology & Department of Forensic Medicine and Toxicology, VIMSAR, Burla, Odisha over a period of 2 years. The liver specimens collected from 64 cases were examined grossly as well as microscopically to establish the presence of liver diseases and also to find out the types of liver diseases.Results: Out of 64 specimens, fatty change, chronic venous congestion, hepatitis, cirrhosis, Steatohepatitis, and drug toxicity cases are reported; fatty change being the predominant finding. Liver diseases predominated in males with male to female ratio of 5:1.Conclusion: Autopsy examination of liver was very helpful to identify silent liver diseases.